Quadratic Equations

marvabeth

New member
Joined
Jan 20, 2009
Messages
1
Hi, I'm new so I hope I post this question correctly. If not, please let me know what I need to fix.

square root of 3x=(square root of 5x plus 1)-1
I squared both sides and got
3x=5x plus 1 minus 2 (square root of 5x plus 1) plus 2

Did I square the terms on the right correctly?
 
> square root of 3x=(square root of 5x plus 1)-1

You need an extra pair of brackets: square root of 3x=(square root of (5x plus 1))-1
Better to use "sqrt": sqrt(3x) = sqrt(5x + 1) - 1

> I squared both sides and got
> 3x=5x plus 1 minus 2 (square root of 5x plus 1) plus 2

Not quite: 9x^2 = 5x + 1 - 2sqrt(5x +1) + 1 : -1 times -1 = 1, not 2 !
 
Top